The relationship between level of knowledge and adherence therapy in hypertensive patients at Ramadhan Pharmacy in Yogyakarta City - Ardiansyah, Ryan; Zukhruf Saputri, Ginanjar; Supadmi, Woro; Candradewi, Susan Fitria; Hastuti, Dwi; Ardhiani, Menit (International Journal of Health Science and Technology, 2023)
The prevalence of hypertension in Indonesia is still high. Several factors, including knowledge and compliance influence the outcome of hypertension therapy. Management of hypertension based on medication adherence is absolutely necessary with the aim of achieving and maintaining blood pressure below 140/90 mmHg. This study aimed to determine the relationship between the level of knowledge and compliance of hypertensive patients at Ramadhan Pharmacy. This study used an analytical observational research method with a cross-sectional approach. Purposive sampling techniques are used to collect data from 78 patients. Data was collected during the period July-August 2022. Respondents were hypertensive patients who met the inclusion criteria, who had been taking antihypertensive drugs for one month and were willing to fill in informed consent. Data collection using validated questionnaire tools, in the form of level of knowledge and adherence to antihypertensive drug therapy (MARS). Data results were analyzed using test statistical analysis Fisher Exact SPSS to determine if there is a relationship between knowledge and compliance. Based on the Fisher Exact Test, respondents had a high level of knowledge, and 73% and 77% of hypertensive patients were obedient to antihypertensive drugs, respectively.  The relationship of knowledge level with adherence to antihypertensive drugs p-value = 0.017 (OR=4,000.95%; CI (1.305- 12.256). The conclusion of this study shows the relationship between knowledge and adherence therapy in hypertensive patients at Ramadhan Pharmacy Yogyakarta. Therefore, the role of pharmacist education is one of the efforts to improve pharmaceutical services for hypertensive patients in improving adherence and success of therapy.